Approaching the land of bliss religious praxis in the cult of Amitābha - Payne, Richard K. 1949-; Tanaka, Kenneth Kenichi 1947- (University of Hawaiʻi Press, 2019)
"It could be argued that cultic practices associated with particular buddhas and bodhisattvas are more representative of the way Buddhists conceive of their relation to tradition. This volume aims to explore this aspect of Buddhism by focusing on one of its most important cults, that of the Buddha Amitabha. Approaching the Land of Bliss is a rich collection of studies of texts and ritual practices devoted to Amitabha, ranging from Tibet to Japan and from early medieval times to the present."--Jacket
Keywords: Amitābha; Geschichte; Ritus; Reines-Land-Schule; Amidismus; Religionsausübung; Ostasien; Amitābha / (Buddhist deity) / Cult; Pure Land Buddhism / editor; Amitābha / (Buddhist deity); Cults; Pure Land Buddhism; Aufsatzsammlung